Association of Serum Retinoic Acid With Risk of Mortality in Patients With Coronary Artery Disease. Issue 4 (5th August 2016) - Liu, Yan; Chen, Hongen; Mu, Di; Li, Di; Zhong, Yuan; Jiang, Nan; Zhang, Yuan; Xia, Min
Abstract : Rationale: : Retinoic acid (RA) and its mediated nuclear receptor signaling have broad protective effects on vascular systems. Whether circulating levels of RA are associated with mortality in patients with coronary artery disease is still unknown. Objective: : To evaluate the association of circulating RA with the risk of mortality. Methods and Results: : We measured serum RA concentrations in 1499 patients with angiographically confirmed coronary artery disease (mean age, 61 years; male, 67%) recruited from October 2008 and December 2011 in the Guangdong Coronary Artery Disease Cohort. During a median (interquartile range) period of 4.4 (3.6 to 6.1) years of follow-up, there were 295 all-cause mortality, among which 208 had cardiovascular mortality. Serum RA level was significantly lower in participants with mortality (median 21 [11–47] nmol/L) than in those without mortality (median 39 [19–86] nmol/L). In multivariate analyses, the hazard ratios for total mortality among those in the lowest (referent) to highest quartiles of serum RA measured at study entry were 1.0, 0.83, 0.74, and 0.56, respectively ( P -trend<0.001). For cardiovascular mortality, the comparable hazard ratios were 1.0, 0.76, 0.69, and 0.60 ( P -trend<0.001). Furthermore, high RA levels (defined as >median) were associated with lower risk of total mortality (adjusted hazard ratios, 0.68; 95% confidence interval, 0.50–0.85; P =0.001) and cardiovascular mortality (adjusted hazard ratios, 0.62; 95% confidence interval, 0.45–0.78; P <0.001) compared with low RA (defined as ⩽median). Conclusions: : Serum RA level was associated with lower risk of mortality in a population-based coronary artery disease cohort. Abstract : Supplemental Digital Content is available in the text.